DIAGNOSTIC APPLICATIONS OF INFRARED THERMOGRAPHY IN CAPTIVE BRAZILIAN CANIDS AND FELIDS - Costa, André Luiz Mota da; Rassy, Fabrício Braga; da Cruz, João Batista (Archives of Veterinary Science, 2020)
ABSTRACT: Infrared thermography is a noninvasive diagnostic imaging method that does not require animal restraint. This tool provides instant images in real time, even at great distances, being very advantageous for wild animals. The thermograph measures the frequency of infrared rays, it locates hot or cold regions in the body tissues, detecting physiological or pathological processes that modify body temperature. In the veterinary diagnosis of wild animals, thermal imaging is used to determine causes of lameness, lesions and inflammation. It also can be used to diagnosis infectious diseases, reproductive period or gestation and to measure animal welfare and stress levels. This research aimed to use infrared thermography as a tool for remote diagnosis in Brazilian canids and felids kept ex-situ at the Sorocaba Zoo, Brazil. During one year the images were recorded biweekly in 42 individuals (18 canids and 24 felids). No thermal change was noticed in the images taken biweekly. Twelve animals presented symptoms at different times, then images were taken immediately and recorded every 3 days to follow the evolution of the clinical signs and treatment. Atypical images were interpreted and correlated with the clinical signs. The method showed good sensitivity when applied to felids. In the canids there was good sensitivity for head and limb disorders, because these regions have shorter hair. It is concluded that thermography is an important diagnostic tool for canids and felids, being an examination carried out at a distance, without stress, non-invasive and painless, prioritizing animal welfare.